Permintaan Kedelai Pada Industri Rumah Tangga Tahu Di Kabupaten Sleman - Farid Styawan; Dwidjono Hadi Darwanto; Lestari Rahayu Waluyati (Agro Ekonomi, 2016)
The needs of domestic consumption of soybean tends increasing every year, one of them for tofu industry inputs. This study aims to determine: 1) the factors that influence the demand for soybean on tofu industry in Sleman Regency, 2) the value-added generated from tofu industry in Sleman Regency, 3) the factors that affect tofu industry profits in Sleman Regency. The method used in this research is descriptive analysis method. This research was conducted in Seyegan districts and Gamping districts in 2016, and taken proportionally 65 people tofu industry as respondents. Factors that affect demand for soybean on tofu industry and the factors that affect tofu profitability were calculated using linear regression analysis, while the value-added on tofu industry calculated using the value-added method of Hayami. The results showed that demand for soybean is influenced by soybean prices, labor costs, the price of firewood, and the ownership status of the milling machine. Then, the value-added of fried tofu is Rp 5.602,4/kg of soybean, the value-added of white tofu is Rp 5.175,2/kg of soybean, and the value-added of yellow tofu is Rp 3.999,6/kg of soybean. The results also showed that the profits of tofu industry in Sleman influenced by labor costs, the price of soybeans, production capacity, business experience, and the price of coagulant.